2004
DOI: 10.1597/03-054.1
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-α and Nonsyndromic Cleft Lip with or without Palate in Brazilian Patients: Results of a Large Case-Control Study

Abstract: These data further suggest that TGFA is not a relevant modifier locus for the occurrence of CL/P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
2
10
1
1
Order By: Relevance
“…1 In this study, the C2 allele frequency was 0.06, similar to that reported in previous case-control studies performed in Brazil. 15,16 Several studies (case-control and case-parent triads) found an association between a TGFA / Taq I polymorphism and clefting; 10,12,17,18 however, other studies did not find an association. [19][20][21][22] We did not find any evidence of association between TGFA / Taq I polymorphisms and oral cleft in the population studied.…”
Section: Discussionmentioning
confidence: 99%
“…1 In this study, the C2 allele frequency was 0.06, similar to that reported in previous case-control studies performed in Brazil. 15,16 Several studies (case-control and case-parent triads) found an association between a TGFA / Taq I polymorphism and clefting; 10,12,17,18 however, other studies did not find an association. [19][20][21][22] We did not find any evidence of association between TGFA / Taq I polymorphisms and oral cleft in the population studied.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the BCL3 and TGFA data have already been included in previous reports. 20,22 Gene -gene interactions were tested using a two-step approach. First, we applied a linkage disequilibrium test to verify if a combination of alleles at two different loci is preferentially present in the considered sample.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were replicated in some studies, but there have been a growing number of reports not confirming this association (revised in). 4,22 Considering that deficiency of folate would cause an impairment on cell proliferation or migration during embryogenesis, we hypothesized that the presence of a maternal CT or TT/ MTHFR genotype together with the embryo C1C2/TGFA or C2C2/TGFA genotypes may favor the occurrence of CL/P. We did not observe any interaction between maternal MTHFR and TGFA offspring genotypes.…”
Section: Gene -Gene Interactionsmentioning
confidence: 92%
“…However, other studies have not been able to replicate this finding by either linkage or association [9,17,18]. Two meta-analyses, one looking at association studies [19] and a more recent study combining 13 genome scan studies [20•], reveal positive results, corroborating the hypothesis that TGFA is a modifier rather than necessary or sufficient to cause clefting.…”
Section: P13 (Tgfa)mentioning
confidence: 99%